88.4k views
4 votes
For f(x)=3x+1 and g(x)=x^2-6, find (f•g)(x).

For f(x)=3x+1 and g(x)=x^2-6, find (f•g)(x).-example-1

1 Answer

4 votes

Answer & Step-by-step explanation:

When we see (f * g)(x), it means that we are going to be multiplying f(x) and g(x) together.

f(x) = 3x + 1

g(x) = x² - 6

(3x + 1)(x² - 6)

Multiply each term from the first parentheses to the second parentheses.

3x³ - 18x + x² - 6

Combine like terms and make sure the expression is in standard form.

3x³ + x² - 18x - 6

So, your answer will be letter choice B.

User Kspearrin
by
6.0k points